Efficacy and Safety of Chloroquine in Patient with COVID-19 : A Comprehensive Systematic Review - Agustina, Agustina; Rahma, Riah (The Indonesian Journal of General Medicine, 2024)
Background: Chloroquine is a potent inhibitor of the SARS Coronavirus (SARS-CoV) and SARS-CoV-2 in in vitro studies, and has been suggested to exhibit antiviral activity against Zika virus, poliovirus, HIV, and influenza viruses A & B. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: No significant beneficial effect of using chloroquine on the outcome of patients with COVID-19.